2008
DOI: 10.1007/s12237-008-9119-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiscalarity of the Nutrient–Chlorophyll Relationship in Coastal Phytoplankton

Abstract: The relationship between nitrogen (N) and phytoplankton chlorophyll a (Chl) establishes a basis for understanding eutrophication in coastal marine ecosystems. A substantial literature exists on cross-ecosystem analysis of this relationship, but there is little information on crossscale patterns. A collection of observational records in Bedford Basin (Canada) was used to construct the N-Chl relationship at four time scales: intra-day, intra-annual, interannual, and interdecadal. Additionally, a dataset of conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 35 publications
4
21
1
1
Order By: Relevance
“…Thus, changes in chlorophyll a concentration in short (diel and intra-annual) and long (decadal) scales could be explained taking into account the corresponding variability in nitrate concentration. However, Li et al (2010) did not find any relationship between interannual variability of nitrate and chlorophyll a. These findings suggest that the mechanisms underlying the nutrient-driven phytoplankton dynamics could vary depending on the time scale considered.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, changes in chlorophyll a concentration in short (diel and intra-annual) and long (decadal) scales could be explained taking into account the corresponding variability in nitrate concentration. However, Li et al (2010) did not find any relationship between interannual variability of nitrate and chlorophyll a. These findings suggest that the mechanisms underlying the nutrient-driven phytoplankton dynamics could vary depending on the time scale considered.…”
Section: Introductioncontrasting
confidence: 56%
“…Cloern (2001) suggested that the optical properties of the water column and/or horizontal transport processes (that depend on several factors like wind, bathymetry, basin geography and river flow) could also contribute to modulate the response to nutrient enrichment. Li et al (2010) reported that the response of chlorophyll a to changing nutrients varied according to the time scale considered. Thus, changes in chlorophyll a concentration in short (diel and intra-annual) and long (decadal) scales could be explained taking into account the corresponding variability in nitrate concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient depletion and increasing zooplankton grazing typically cause breakdown of spring blooms and maintain low phytoplankton biomass during summer; and in nutrient-rich systems grazing-resistant algal species can give rise to a second bloom later in the year (Sommer et al 1986). In temperate lakes (Reynolds 2006), oceans (Longhurst 1995) and coastal basins (Longhurst 1995;Li et al 2010), a secondary bloom in autumn is often fuelled by transport of nutrientrich deep waters to the surface as stratification is eroded by surface cooling and convective mixing. Further, in turbid estuaries where phytoplankton is controlled by light availability, winter blooms can be triggered by increasing solar penetration caused by a reduction of suspended sediments owing to low river inflow or reduced wind stress (Guinder et al 2009).…”
Section: Annual Cycles Of Phytoplankton Biomassmentioning
confidence: 99%
“…As well as true deviations from a long-term average seasonal pattern, the residual component also includes variability associated with sampling errors that can be large when single measurements are used as estimators of monthly mean Chl-a concentration. Phytoplankton communities and biomass change on many scales at the same time (Li et al 2009). Large changes can occur at timescales shorter than a month (e.g., Abreu et al 2009), and monthly scale changes in Chl-a can arise from processes operating at shorter timescales (Lucas and Cloern 2002).…”
Section: Event-scale Variabilitymentioning
confidence: 99%